Effectiveness of gender policies in achieving gender equality in ocean science programmes in public universities in Kenya. (October 2022) - Ojwala, Renis Auma; Kitada, Momoko; Neat, Francis; Buckingham, Susan
Abstract: The recently proclaimed Ocean Decade by the United Nations General Assembly is committed to gender equality and women's empowerment in ocean science research and governance. This paper examines the status of gender equality in ocean science research across higher education institutes in Kenya. Kenya has ratified international conventions for gender equality and developed national and institutional gender equality and sexual harassment policies as its commitment to promoting equitable access to education. However, it is poorly understood whether the implementation of these policies has been successful at the institutional level. This study explores the effectiveness of the institutional gender policies in public universities delivering ocean science-related degrees. Existing policies were analysed using the Gender Integration Continuum and gender ratios of enrolled students and recruited staff in ocean science-related fields investigated. The study identified that while some policy provisions included gender-transformative strategies to increase women in science-related courses, many were outdated. Gender-disaggregated data showed fewer female students and female staff in management positions compared to men. Additionally, the proportion of women in academic posts declined with the seniority of employment level, and women were more likely than men to occupy non-tenured positions. In conclusion, it appears that the presence of gender policies does not necessarily translate to gender balance across the universities. We offer some explanations as to why this should be and where to direct future research needs.